2014
DOI: 10.1016/j.nbd.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial increase of reactive nitrogen species in the kainate model of temporal lobe epilepsy

Abstract: Steady-state levels of reactive oxygen species (ROS) and oxidative damage to cellular macromolecules are increased in the rodent hippocampus during epileptogenesis. However, the role of reactive nitrogen species (RNS) in epileptogenesis remains to be explored. The goal of this study was to determine the spatial and temporal occurrence of RNS i.e. nitric oxide levels in a rat model of temporal lobe epilepsy (TLE). Rats were injected with a single high dose of kainate and monitored by video for behavioral seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 57 publications
5
45
0
Order By: Relevance
“…In studies of patients with TLE, the role of mitochondria has been suggested by inhibition of complex I of the electron transport chain (ETC) and reduction in N-acetyl aspartate levels in the hippocampus (Kunz et al, 2000; Vielhaber et al, 2008). Recent work from our group has shown increases in production of mitochondrial ROS, reactive nitrogen species (RNS), oxidative damage to oxidant-sensitive mitochondrial proteins (aconitase and complex I) and glutathione depletion in animal models of TLE (Jarrett et al, 2008; Waldbaum et al, 2010; Ryan et al, 2012, 2013). Increased mitochondrial ROS and oxidative damage to ETC enzymes suggests that mitochondrial respiration may be impaired in TLE.…”
Section: Introductionmentioning
confidence: 99%
“…In studies of patients with TLE, the role of mitochondria has been suggested by inhibition of complex I of the electron transport chain (ETC) and reduction in N-acetyl aspartate levels in the hippocampus (Kunz et al, 2000; Vielhaber et al, 2008). Recent work from our group has shown increases in production of mitochondrial ROS, reactive nitrogen species (RNS), oxidative damage to oxidant-sensitive mitochondrial proteins (aconitase and complex I) and glutathione depletion in animal models of TLE (Jarrett et al, 2008; Waldbaum et al, 2010; Ryan et al, 2012, 2013). Increased mitochondrial ROS and oxidative damage to ETC enzymes suggests that mitochondrial respiration may be impaired in TLE.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal lobe epilepsy (TLE), the most common form of acquired epilepsy, is characterized by recurrent seizures that originate from the hippocampus, amygdala or entorhinal cortex (EC) and is initiated by an injury, such as head trauma, hypoxia, complex febrile seizures or status epilepticus (SE) [1,2]. Epilepsy involves several processes, such as neuronal loss, gliosis, gene regulation, axonal sprouting, inflammation and neurogenesis [1].…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy involves several processes, such as neuronal loss, gliosis, gene regulation, axonal sprouting, inflammation and neurogenesis [1]. However, the molecular mechanism of epileptogenesis is not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases it closely mimics the clinical manifestations of mesial temporal lobe epilepsy in humans, the most common type of epilepsy in adults (Sharma et A c c e p t e d M a n u s c r i p t proposed that only severe neuronal damage cannot explain the consequential epileptic activity, so, subcellular structural, molecular and nano modifications, facilitating abnormal firing and seizure episodes should be present (Ryan et al 2014, Otahal et al 2014). Different approaches could be used to reveal such fine modifications.…”
Section: Introductionmentioning
confidence: 91%